Full spectrum x-ray mapping reveals differential localization of salt in germinating seeds of differing salt tolerance - Guja, Lydia; Wuhrer, R.; Moran, K.; Dixon, K.; Wardell-Johnson, Grant; Merritt, David (Wiley-Blackwell Publishing Ltd, 2013)
Seeds of many coastal plants can survive exposure to seawater and may be dispersed long distances by the ocean. The salt tolerance or avoidance strategies of seeds are poorly understood, even though these traits may fundamentally influence dispersal and recruitment in coastal dunes. This research aimed to demonstrate how salt exclusion or localization within germinating seeds may affect salt tolerance. To determine the response of seeds to external salinity during imbibition (water uptake), it was necessary to quantify uptake and spatially resolve the internal distribution of salt. Flame photometry was used to quantify salt concentration in imbibing seeds and a new application of full-spectrum X-ray mapping allowed visualization of the spatial distribution and relative abundance of salt. As external salinity increased, salt-sensitive Spyridium globulosum (Rhamnaceae) seeds accumulated sodium and chlorine in the seed embryo, while potassium was increasingly displaced and germination was reduced. Conversely, salt-tolerant Ficinia nodosa (Cyperaceae) seeds avoided ion uptake and germination was not affected by imbibition in high sodium chloride (NaCl) concentrations. These results provide insight into mechanisms of salt tolerance/avoidance during imbibition and early germination and suggest that oceanic dispersal can be a viable explanation for the distribution of some plant species.